AN OVERVIEW OF STATINS AS HYPOLIPIDEMIC DRUGS (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
There is a wealth of evidence suggesting association between Dyslipidemia and Heart Failure. Statins are the treatment of choice for the management of Dyslipidemia because of their proven efficacy and safety profile. They also have an increasing role in managing cardiovascular risk in patients with relatively normal levels of plasma cholesterol. The article reviews the role of Statins in the treatment of Dyslipidemia. Although all statins act by act by blocking the HMG-CoA reductase enzyme, which catalyzes the rate-limiting, step in de novo cholesterol synthesis, they differ in terms of their chemical structures, pharmacokinetic profiles, and lipid-modifying efficacy. Lovastatin, Pravastatin and Simvastatin are derived from fungal metabolites and have elimination half-lives of 1–3 h. Atorvastatin, Cerivastatin (withdrawn from clinical use in 2001), Fluvastatin, Pitavastatin and Rosuvastatin are fully synthetic compounds, with elimination half-lives ranging from 1 h for Fluvastatin to 19 h for Rosuvastatin. As a class, statins are generally well tolerated and serious adverse events, including muscle toxicity leading to rhabdomyolysis, are rare. Consideration of the differences between the statins helps to provide a rational basis for their use in clinical practice.